Risk Analysis of Malpractice at Central General Hospital Friendship Jakarta - Baik Marpikir Manalu, Marsada; Markoni, Markoni (Ann Publisher, 2023)
In the world of health services, many risks may be used as legal cases, ranging from the arrival of patients' data collection until patients leave the place of service. Europe and America have characteristics of different types of malpractice incidents, and in Asia, there are both developed, developing, and underdeveloped countries. This study aims to examine and analyze the prevention of malpractice risk and the mechanism of malpractice risk at Friendship Center General Hospital. The research methods used are empirical and conceptual juridical research methods. Researchers use literature studies as a tool for collecting research materials. The results of the study found that Permenkes 11 of 2017 states that Patient Safety aims to improve the Quality of Service in health Service Facilities through the application of Risk Management in all Aspects of Health Services, which means that it is expected that with the application of good Risk management, the risk for complaints that lead to malpractice reporting in any form can be suppressed in such a way. Although the application of standard operating procedures in hospitals, the risk of malpractice complaints is still possible due to many things from various angles that cannot be explained in the regulations or cannot be explained due to other things regarding the ability of doctors/service officers to convey information about problems or obstacles obtained at the hospital including facilities and other unwritten rules, So even though it has been prepared in such a way, the risk still occurs.